1999
DOI: 10.1111/j.1432-2277.1999.tb00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term maintenance of therapeutic cyclosporine levels leads to optimal graft survival without evidence of chronic nephrotoxicity

Abstract: Since the introduction of cylcosporine into clinical use, a major area of concern within the transplant community has been the fear of chronic nephrotoxicity. Although progressive renal damage does appear to occur in native kidneys of heart and liver transplant patients receiving cyclosporine, it has been our contention that its use is not a major cause of deterioration in renal allografts. We therefore undertook a study of 91 consecutive renal transplants performed over a three-year period with a minimum graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…When an insensitive surrogate marker such as serum creatinine or GFR is used (22), the apparent prevalence is less common (7,8,23). In nonrenal solid organ transplantation (2,21,24) or with CsA treatment for autoimmune diseases not involving the kidney (25), declining renal function attributable to CsA nephrotoxicity is becoming an increasingly recognized and common problem.…”
Section: Discussionmentioning
confidence: 99%
“…When an insensitive surrogate marker such as serum creatinine or GFR is used (22), the apparent prevalence is less common (7,8,23). In nonrenal solid organ transplantation (2,21,24) or with CsA treatment for autoimmune diseases not involving the kidney (25), declining renal function attributable to CsA nephrotoxicity is becoming an increasingly recognized and common problem.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate or variable CsA exposure is now believed to be a key determinant of acute rejection, which in turn is closely linked to the development of chronic rejection, the principal cause of late graft loss (19,(25)(26)(27)(28)(29)(30)(31)(32). Recent studies have shown that patients differ substantially in the relative absorption of CsA from cyclosporine microemulsion, providing a logical basis for the definition of patient risk categories according to absorber status (15,21).…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate or variable CsA exposure is now believed to be a key determinant of acute rejection, which in turn is closely linked to the development of chronic rejection, the principal cause of late graft loss; early and long-term graft survival may therefore both be critically dependent upon achieving and maintaining adequate CsA exposure in the early posttransplant period (4,(26)(27)(28)(29)(30). This nested pharmacokinetic study was conducted in the first 3 months post-transplant in renal transplant patients receiving basiliximab immunoprophylaxis and cyclosporine microemulsion maintenance immunosuppression to determine the relationship between cyclosporine dose and pharmacokinetics and to determine the optimal predictors for absorption profiling in clinical practice.…”
Section: Discussionmentioning
confidence: 99%